Oral Health in a Changing Climate: A Scoping Review of Global Evidence (Bangladesh Journal of Medical Science, 2026)
Climate change is being recognized as a determinant of human health, yet its impact on oral health is underexplored. This scoping review aims to map the existing literature on the impact of climate change on oral health and dental practice and highlight key knowledge gaps. The literature search was conducted in the PubMed and Dimensions databases and supplemented by manual screening of the references of included studies. In total, 23 articles were included. Most of the articles published after 2019 reflect the field’s emerging nature. The evidence indicates that climate change affects oral health through multiple direct and indirect pathways, including environmental and biological mechanisms. Vulnerable groups- children, older adults, low-income populations, rural communities, and those in low- and middle-income countries (LMICs) are identified as being at more substantial risk. The findings suggest that the field is in an early conceptual stage, characterized by narrative and opinion-based literature and limited empirical research. The evidence also suggests a bidirectional relationship: while climate change affects oral health and dental services, dental practice itself contributes to environmental burden. Although plausible pathways are well described, causal evidence remains scarce. This review highlights the need for interdisciplinary, empirical research, greater attention to under-studied regions, and integration of oral health into climate adaptation and sustainability policies.BJMS, Vol. 25 No. 02 April’26 Page: 400-412